HIJAB SEGITIGA AKUNTAN UNTUK MELAWAN KORUPSI - Sari, Arista Fauzi Kartika (Jurnal Ekonomi Modernisasi, 2016)
This article aims to create a concept can be used by accountants to fight corruption by a hijab. The concept consists of three things; spiritual, ethical and love. They are an influential interconnected with each other and form a Hijab Triangle. Hijab Triangle serves as a shield modern accounting value, ie materialistic and egoistic to affect inward accountants in soul and thought. It can cause an accountants doing corruption. Hijab triangle can also make accountants more "beautiful" in the characteristic and behavior, and increase in the sight of God. This hijab should be applied before becoming an accountant or in the accounting student, by accountant educators.